A Severe Gastroenteritis Outbreak of Salmonella enterica Serovar Enteritidis Linked to Contaminated Egg Fried Rice, China, 2021 - Zhang, Yaowen; Liu, Kangkang; Zhang, Zhenbiao; Tian, Sai; Liu, Xiong; Qi, Hongjuan; Dong, Derong; Wang, Yong; Liu, Meiling; Li, Xinge; Han, Yiran; Zhu, Kunpeng; et al. (Frontiers in Microbiology, 2021)
Salmonella contamination of eggs and egg shells has been identified as a public health problem worldwide. Here, we reported an outbreak of severe gastrointestinal symptoms caused by Salmonella enterica serovar Enteritidis (S. enteritidis) in China. We evaluated the outbreak by using epidemiological surveys, routine laboratory testing methods, and whole genome sequencing (WGS). The outbreak had characteristical epidemiological and clinical features. It caused a very high attack rate (69.4%) in a short incubation time. All patients developed diarrhea and high fever, accompanied by abdominal pain(62.3%), nausea(50.4%), and vomiting(62.7%). The average frequency of diarrhea was 12.4 times/day, and the highest frequency of diarrhea was as high as 50 times/day. The average fever temperature was 39.4℃, and the highest fever temperature was 42℃. Twenty strains of S. enteritidis were recovered, including 19 from the patients samples, and one from remained egg fried rice. Antibiotic susceptibility test showed that the 20 outbreak strains all had the same resistance pattern. PFGE results demonstrated that all 20 strains bore completely identical bands. Phylogenetic analysis based on WGS revealed that all outbreak 20 strains were tightly clustered together. So the pathogenic source of this food poisoning incident may be contaminated egg fried rice. Resistance gene analysis showed that the outbreak strains are all multi-drug resistant strains. Virulence gene analysis indicated that these outbreak strains carried a large number of virulence genes, including 2 types of Salmonella pathogenicity islands (SPI-1 and SPI-2). Other important virulence genes were also carried by the outbreak strains, such as pefABCD, rck and shdA. And the shdA gene was not in other strains located in the same evolutionary branch as the outbreak strain. We speculated that this is a significant reason for the serious symptoms of gastroenteritis in this outbreak. This outbreak caused by S. enteritidis suggested government should strengthen monitoring of the prevalence of outbreak clone strains, and take measures to mitigate the public health threat posed by contaminated eggs.